Physics, Simulation, and Experiment of Perovskite Solar Cells with Addressing Hysteresis Effect. Issue 11 (31st August 2022) - Ai, Zhenhai; Wu, Donghui; Ma, Tianshu; Zhao, Yue; An, Yidan; Wang, Changlei; Li, Xiaofeng
Abstract : The hysteresis effect is a critical factor affecting the widespread application of perovskite solar cells (PSCs). To eliminate this adverse effect, it is necessary to uncover the underlying physics, which characterize the microscopic behaviors of electrons, holes, and ions within PSCs. Herein, addressing the hysteresis effect of PSCs, the migration mechanisms of mobile ions (i.e., anions and cations) within the perovskite layer is explored, the simulation model is developed, and the corresponding experiments are performed. The electromagnetic response, the transport of electrons, holes, anions, and cations, and the electrostatic characteristics determined by the charges are considered in detail. The simulation verifies that the performance degradation is indeed originating from the mobile ions, especially under a high ion concentration. The physical reason of the unbalanced performance under forward and reverse electric scans is presented by optoelectronic simulation. The manipulation of the hysteresis effect increasing the built‐in electric field and reducing the hysteresis index (HI) of low ion concentration devices, but increased HI under a high ion concentration is further investigated. The simulation guides the fabrication of a normal‐bandgap PSC, which achieves the reverse (forward) power‐conversion efficiency up to 23.35% (22.22%) with a HI as low as 4.8%. Abstract : The underlying physics and limiting factors of low‐performance and high‐hysteresis perovskite solar cells are disclosed by a comprehensive optoelectronic simulation with ion migration, which enables the manipulation of the device as well as the realization of high power conversion efficiency and low hysteresis index in the experiment.